The Application of Hopkins' theory of inscape to three of his sonnets, "God's Grandeur", "Hurrahing in Harvest", and the one beginning with As kingfishers catch fire - Hines, George G (University of Ottawa (Canada), 1968)
Abstract not available.
Keywords: Literature, English.